The dinosaur book. - Le Roi, David frey50; Zanini, Giuseppe In the days of the dinosaurs; Bertelli, G. B. Ill. (Greenwich House New York, 1983)
Traces the development of life on earth, from the first living things through early plants, land animals, lizards, and mammals, to the appearance of man.
Adaptation of: In the days of the dinosaurs / G. Znini. 1971
Keywords: Dinosaurs -- Juvenile literature; Prehistoric animals